Future perfect? : God, medicine and human identity - Deane-Drummond, Celia; Scott, Peter, 1961- (T & T Clark International, 2010)
A hugely topical collection of essays from a cross-disciplinary group of leading academics focussing on the implications for an understanding of human identity in light of the current possibilities in medical science. The book brings together an international body of medical experts alongside philosophers, sociologists, theologians and ethicists in order to discuss these vital issues. The ensuing discussion will allow public debate to be more informed about the actual possibilities inherent in medical science, alongside a sophisticated treatment of ethical and theological issues. The result i.